Dynamic paraspinal muscle impingement causing acute hemiplegia after C1 posterior arch laminectomy: A case report. Issue 50 (December 2017) - Notani, Naoki; Miyazaki, Masashi; Yoshiiwa, Toyomi; Ishihara, Toshinobu; Kanezaki, Shozo; Tsumura, Hiroshi
Abstract: Rationale: Acute neurological deficits following spinal surgery commonly result from epidural hematoma, surgical trauma, vascular compromise, and graft or hardware impingement, with the cause identified by magnetic resonance imaging (MRI). We present a rare case of dynamic paraspinal muscle impingement after C1 posterior arch laminectomy, which was diagnosed by myelography, with no significant findings on MRI. Patient concerns: An 81-year-old, severely obese male, was referred to our department for the treatment of vertebral disease of the lumbar spine. The patient presented with bilateral weakness and numbness of the upper extremities and gait disturbances. Based on MRI, a diagnosis of retro-odontoid pseudotumor was made, and C1 posterior arch laminectomy, in combination with C4 partial laminectomy and C5 to C6 laminoplasty, was performed. On postoperative day 3, the patient's neurological status deteriorated, with right upper extremity and right lower extremity weakness increasing with neck extension. Although there was no evidence of epidural hematoma formation on MRI, obstruction of the flow of contrast medium by an external posterior compression in neck extension at the level of C1 was identified by myelography. Revision surgery was performed and local muscle swelling at the surgical site identified with no hematoma formation. Occiput to C3 fixation, with instrumentation, was performed. Outcomes: Muscle strength of the right upper extremity and lower extremities recovered postsurgery, and the patient has continued to improve function 3 years after surgery, with no further neurological episodes. Lessons: Dynamic paraspinal muscle impingement following C1 laminectomy in a muscular man was diagnosed by myelography, with no significant findings on standard MRI. Conclusion: The possibility of dynamic paraspinal muscle impingement should be considered in patients developing acute, progressive, neurological deficits after posterior cervical decompression, with myelography being the imaging method of choice for diagnosis.